A solder, high strength steel workpiece, laser welded joint and method of making the same

By adding Fe and C-based solder to the molten pool during laser welding, the problem of joint weakening caused by ferrite structure in the weld was solved, achieving high-strength and tough laser-welded joints while reducing costs and process complexity.

CN120551642BActive Publication Date: 2025-10-21SHANGHAI INST OF OPTICS & FINE MECHANICS CHINESE ACAD OF SCI

Patent Information

Application Number
CN202511063878.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-31
Publication Date
2025-10-21
Estimated Expiration
2045-07-31

AI Technical Summary

Technical Problem

When welding steel with aluminum or aluminum alloy coatings on the surface, existing technologies tend to form ferrite structures in the weld, which weakens the joint. Furthermore, traditional methods are costly and complex, making it difficult to guarantee the high strength and toughness of the welded joint.

Method used

Using a welding material mainly composed of Fe and C, it is gradually added to the molten pool during the laser welding process. Through the solid solution strengthening effect of C, a high-performance laser welded joint is formed, ensuring that the volume fraction of martensite in the weld is not less than 90% and the average mass fraction of C element is not less than 0.28%, while reducing the addition of other alloying elements.

Benefits of technology

It significantly improves the mechanical properties and stability of weldments, reduces manufacturing costs, ensures the reliability and adaptability of weld performance, and has excellent fracture strength and elongation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120551642B_ABST
    Figure CN120551642B_ABST
Patent Text Reader

Abstract

The present application relates to the manufacture of high-strength steel coated plate welded parts, in particular to a welding material, a high-strength steel workpiece, a laser welded joint and a manufacturing method thereof. The composition of the welding material satisfies the following conditions in terms of percentage by weight: C is greater than or equal to 0.5%, trace alloying elements are 0-0.36%, the content of Mn and Si is less than or equal to 2%, 6% is greater than or equal to 5C+Mn and is greater than or equal to 2.5%, and the rest is Fe and inevitable other elements; the trace alloying elements are at least one of Nb, V and Ti elements, and the content of Nb, V and Ti elements is less than or equal to 0.12%. The method does not need to remove the aluminum coating, utilizes the solid solution strengthening effect of C, and makes the volume fraction of lath martensite in the final weld after quenching greater than or equal to 90%. This scheme reduces the addition of alloying elements, reduces the cost and process control difficulty, avoids the formation of coarse carbides, improves the mechanical properties and stability of the joint, has high fracture strength and elongation, and realizes the double improvement of the strength and toughness and economy of the joint.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the manufacture of high-strength steel coated plate welding components, in particular to a solder, a high-strength steel workpiece, a laser welding joint and a manufacturing method thereof. Background Art

[0002] In certain fields, particularly in the manufacture of automotive and aerospace parts, materials must exhibit high corrosion resistance, leading to the increasing use of materials with surface coatings. Steel coated with aluminum or aluminum alloys, manufactured through cold or hot rolling, not only exhibits excellent corrosion resistance but also exhibits high high-temperature resistance, making it advantageous for the manufacture of certain components using hot working methods. Therefore, aluminum alloy-coated steel sheets are particularly used in the manufacture of automotive bodies and structural components such as door reinforcements, B-pillars, and roof reinforcements. This is particularly true in the application of ultra-high-strength hot-stamped sheet metal, achieving high corrosion resistance, reducing vehicle weight, and improving collision energy absorption.

[0003] In the automotive industry, to reduce vehicle weight and achieve lightweighting goals, an increasing number of materials, whether of equal or unequal thickness and homogeneous or heterogeneous, are welded together before being hot stamped to achieve greater weight reduction and cost savings. Laser welding is a preferred method for this purpose, offering higher quality, greater efficiency, and greater flexibility. These components are known as "laser-welded blanks." High-strength, fully martensitic steel structures are typically produced by laser butt-welding flat workpieces and then hot stamping and quenching the welded seams. During hot stamping, the weld seam is heated to above the AC3 temperature of the steel workpiece for complete austenitization. However, this high temperature inevitably leads to surface oxidation and decarburization of the bare steel, resulting in reduced structural performance. Therefore, surface coating is also necessary, with aluminum or aluminum alloy coatings being widely used in this process. Patent CN101583486B, for example, describes this material in detail.

[0004] However, the manufacture of laser-welded blanks with aluminum or aluminum alloy coatings presents significant challenges. When the weld surface is coated with aluminum or aluminum alloy, the initial coating can enter the molten zone, particularly the weld seam. This can lead to the formation of high-temperature ferrite during cooling. Even after cooling and undergoing high-temperature austenitization, this structure can remain in the final weld, weakening the joint and degrading its performance. Under subsequent mechanical loads, this large amount of ferrite can become the initial site of failure cracks, severely weakening the load-bearing capacity of the welded joint and potentially causing it to break directly at the weld under load. Therefore, improving joint performance and strengthening the weld are essential.

[0005] Patents CN101426612B, 106334875A, etc. remove the surface coating by mechanical methods, laser methods or other methods in advance to prevent it from entering the weld. However, this method has problems such as high cost and complex process.

[0006] Patent CN106392328B discloses a method for welding aluminum-silicon coated hot-formed steel under shielding gas conditions. This patent uses an oxidizing gas to combine with the aluminum in the coating during the welding process to produce aluminum oxide, which has no effect on weld toughness. However, during the welding process, the time it takes for the metal to melt, form a molten pool, and then solidify into a weld is very short. This limits the reaction time between the oxidizing gas and the aluminum. Once aluminum that has not reacted with the oxidizing gas enters the molten pool, it will accumulate within the pool, reducing the toughness and strength of the weld and posing a risk of cracking in the hot stamped parts.

[0007] Patent CN 106488824 B discloses a method for joining two blanks using a filler wire welded from a stainless steel alloy containing the following composition by weight: 0%-0.3% carbon, 0%-1.3% silicon, 0.5%-7% manganese, 5%-22% chromium, 6%-20% nickel, 0%-0.4% molybdenum, 0%-0.7% niobium, and the remainder iron and unavoidable impurities. This method uses a combination of laser and arc welding, which increases heat input and the likelihood of thermal deformation, hindering the joining of thin sheets. Furthermore, the welding speed of this combined laser and arc welding method is limited, reducing production efficiency.

[0008] CN 111432975 A discloses a welding wire filled with the following composition by weight: 0.03% carbon, 0.5% silicon, 1.8% manganese, 20.5% chromium, 25% nickel, 4.7% molybdenum, less than 0.05% sulfur, less than 0.05% phosphorus, and 1.6% copper. When this welding wire is used as a filler material, the high chromium content can lead to the formation of ferrite in the weld zone of the hot-stamped tailor-welded blanks, resulting in a decrease in the mechanical properties of the welded joint, making it impossible to guarantee product quality and posing a high risk of weld failure.

[0009] CN 112368105 A discloses a method for laser welding coated steel blanks using a filler wire. The filler wire contains nickel, chromium, and carbon in weight percentages of 1.68-10.48%, 0-2.70%, and 0.91-2.00%, respectively. The high carbon content in the filler wire results in an excessively high carbon content in the tailor-welded area, reducing plasticity and impact properties, as well as reducing the corrosion resistance of the weld and the service life of the tailor-welded blank.

[0010] CN 108025400 A discloses a laser welding method for semi-finished plates of hardenable steel with an aluminum-based or aluminum-silicon-based coating. The method utilizes a filler electrode that is heated using a separate heat source before the base material melts and then transported into the molten weld to control weld performance. The entire process requires a second heat source, and the weld width must be controlled to be at least 0.15 mm. The weld penetration must also be controlled to account for more than 20% of the material. This requires a large amount of solder, and the multiple control processes are complex. The external heat source also increases the overall process cost. In this method, a filler electrode containing a combined weight percentage of Cr and Mo of 0.5 to 2.0 and a weight percentage of Ni of 1 to 4 is used. The addition of Mo and Cr can easily lead to carbide precipitation in the weld, increasing joint brittleness and making the performance unstable.

[0011] CN 104994989 A discloses a welding wire filled with the following composition by weight: 0.05-0.15% carbon, 0.5-2.0% silicon, 1.0-2.5% manganese, 0.5-2.0% chromium and molybdenum, 1.0-4.0% nickel, and the balance iron and unavoidable impurities. This welding wire contains low levels of chromium and molybdenum. Welded joints using this filler wire exhibit poor hardenability and corrosion resistance. Furthermore, the effects of ferrite cannot be completely suppressed during high-temperature heat treatment, increasing the risk of failure in the weld and heat-affected zone.

[0012] CN104023899B discloses a laser welding method for plates of unequal thickness or strength using a filler wire. The filler wire does not produce a ferrite structure at 900-950°C. The filler wire is primarily composed of carbon or manganese, with the carbon content of the filler wire being 0.1wt% to 0.8wt% higher than the carbon content of the base material of the coated steel plate, and the manganese content of the filler wire being 1.5wt% to 7.0wt% higher than the manganese content of the base material of the coated steel plate. Those skilled in the art are aware that the Mn content of hot-formed steel ranges from 1.0% to 2.5%, meaning the Mn content of the welding wire ranges from 2.5% to 9.5%. A high Mn content can easily lead to Mn segregation in the weld during austenitization, producing a variety of complex carbides, making the weld brittle and unstable. Furthermore, the addition of a large amount of Mn can easily lead to segregation during the welding wire manufacturing process, increasing manufacturing complexity.

[0013] CN 112548395 A and US 20210008665 both disclose a welding wire for laser wire welding, a preparation method, and a tailor-welded blank process. This method involves filling a welding wire with a high carbon content and simultaneously adding high contents of alloying elements such as Ni, Cr, and Mo. This undoubtedly increases the complexity of welding and the difficulty and high cost of producing the welding wire. The overall manufacturing cost is high, the process control is more complicated, and the addition of multiple alloying elements undoubtedly increases the manufacturing cost.

[0014] Currently, laser welding wires for coated steel blanks typically require specialized laser processes or equipment to achieve improved weld quality. Furthermore, the added wires are primarily composed of multiple alloying elements, including C, Cr, Ni, Mo, Mn, and Si. This type of wire not only fails to fully guarantee stable and excellent mechanical and corrosion properties in the welded parts, but also suffers from work hardening during the wire drawing and forming phase, resulting in low wire yields and significant manufacturing difficulties. Furthermore, the complex ratios of these alloying elements are difficult to effectively control during the process, which can easily lead to substandard weld performance. The more expensive Mo element also increases manufacturing costs. Furthermore, another study by the applicant utilizes Ni to expand the austenite region of the weld to suppress ferrite formation. However, Ni is an expensive strategic metal and has a high cost. Therefore, a relatively low-cost method is needed to achieve high-efficiency laser welding of surface-coated steel sheets while ensuring high-strength and high-toughness laser welded joints. Summary of the Invention

[0015] The present invention provides a solder, a high-performance laser welded joint, and a manufacturing method. Without removing the surface aluminum coating, a solder primarily composed of Fe and C is added to the molten pool during the welding process. The solid solution strengthening effect of C is utilized to ultimately produce a high-performance laser welded joint. The final weld, after quenching, has a lath martensite volume fraction of no less than 90%, an average mass fraction of the solid solution strengthening element C of no less than 0.28%, an average mass fraction of Al of 0.72% to 1.2%, and an average mass fraction of C of no less than 120% of the C content of the steel plate base material. This significantly improves the mechanical properties and stability of the weld. By adding a solder primarily composed of Fe and C to the molten pool during the welding process, this method significantly reduces the addition of other alloying elements. The solid solution strengthening effect of C improves joint performance. Furthermore, C is relatively low-cost and does not require complex alloying elements, thus reducing welding material costs. Furthermore, the savings in other alloying elements also reduces the complexity of welding material formulations and the difficulty of process control during the manufacturing process. The present invention mainly adds Fe and C elements without a large amount of additional alloying elements, which can reduce the formation of other coarse carbides in the final weld. At the same time, the carbon-manganese compound formed can be largely dissolved in the subsequent austenitization process, reducing the adverse effects of Mn segregation, and ultimately improving the mechanical properties of the joint; at the same time, it can ensure the removal of ferrite in the final weld, retaining a weld structure with more than 90% martensite, and ensuring the weld performance. However, in the actual welding process, there is often an uncertain assembly gap. When adding solder with other alloying elements, it is often easy to cause incomplete matching and poor solder adaptability. The solder and method of the present invention can ensure that a highly reliable and stable weld is formed under different assembly gaps, and has excellent fracture strength and elongation. By replacing elements such as Ni, Mn, Cr, and Mo with C, a significant reduction in manufacturing costs can be achieved. The overall idea is to improve the joint toughness through the solid solution strengthening effect of high C elements entering the weld, thereby achieving a significant improvement in the overall joint performance.

[0016] The present invention provides the following solutions:

[0017] In a first aspect, the present invention provides a laser welding solder for laser welding joints, wherein the composition of the solder satisfies, by weight percentage: C ≥ 0.5%, trace alloying elements 0-0.36%, Mn and Si contents both ≤ 2%, 6% ≥ 5C + Mn ≥ 2.5%, and the remainder is Fe and other unavoidable elements; the trace alloying elements are at least one of Nb, V, and Ti, and the contents of Nb, V, and Ti do not exceed 0.12%.

[0018] According to a specific embodiment, the composition of the solder is: 0.5%≤C content≤0.8%, 0.48%≤Mn content≤2%, 0.2%≤Si content≤2%, 6%≥5C+Mn≥3.5%.

[0019] Preferably, the Si content in the solder composition is ≤1%.

[0020] Preferably, the content of Mn in the solder is 1%≤2%.

[0021] In a second aspect, the present invention provides a laser welded joint. When two steel plate base materials are butt-jointed for laser welding, the laser welding solder described in the first aspect is added to the molten pool to form an initial weld. The initial weld is quenched to form the laser welded joint, wherein at least one steel plate is a steel plate with an aluminum coating or an aluminum alloy coating, and the final weld of the laser welded joint meets the following conditions: the volume fraction of the internal lath martensite is not less than 90%, the average mass fraction of the solid solution strengthening element C is not less than 0.28%, the average mass fraction of the Al element is 0.72%~1.2%, and the average mass fraction of the C element is not less than 120% of the C content of the steel plate base material.

[0022] The average mass fraction of the C element in the final weld is preferably 120% to 400% of the C content of the steel plate base material, more preferably 130% to 250% of the C content of the steel plate base material, and the absolute value of the difference between the average mass fraction of the Mn element and the Mn element content of the steel plate base material is preferably not more than 1.5%, more preferably not more than 1%.

[0023] The volume fraction of the inner lath martensite of the final weld is preferably not less than 92%, more preferably not less than 95%.

[0024] Preferably, the final weld front reinforcement h1 and the final weld back reinforcement h2 formed by the laser welding joint do not exceed 0.3 mm, and the quenching method is die stamping cooling.

[0025] In a third aspect, the present invention further provides a method for manufacturing a laser welded joint, the method comprising the following steps:

[0026] Step 1: Provide two steel plate base materials, at least one of which is a steel plate with aluminum coating or aluminum alloy coating, and butt the two steel plates together;

[0027] Step 2: Laser welding the butted steel plates, wherein the solder described in the first aspect is added to the molten pool during the welding process to form an initial weld;

[0028] Step 3: quenching and cooling the initial weld to obtain the laser welded joint described in the second aspect;

[0029] During the laser welding process in step 2, the melting volume of the two steel plates is V1, the volume of the solder in the molten pool is V2, and V1 and V2 satisfy 0.03≤V2 / V1≤0.6.

[0030] Preferably, in step 2, the solder is a welding wire, and the welding speed S1 and the wire feeding speed S0 during the welding process satisfy the following relationship:

[0031] 0.04≤ ≤0.3, where d is the wire diameter, d ranges from 0.6-1.6mm and exceeds twice the assembly gap width B, B ranges from 0-0.5mm, S1 is not less than 2.5m / min, B1 is the average width of the upper and lower surfaces of the weld formed, S0 ranges from 1.0-4.5m / min, and t is the average thickness of the two steel plates.

[0032] In a fourth aspect, the present invention provides a high-strength steel workpiece, which is composed of two steel plate base materials and a laser welding joint as described above for connecting the base materials; when the high-strength steel workpiece is subjected to a tensile test, it breaks and fails in the base material area, and the elongation at fracture is not less than 5%.

[0033] Compared with the existing technology, the solder of the present invention reduces the addition of alloy elements, reduces costs and process control difficulty, avoids the formation of coarse carbides, improves the mechanical properties and stability of the joint, and has both high fracture strength and elongation, thereby achieving both improved joint strength and toughness and economic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0035] Figure 1 Shown is a schematic diagram of a cross section of a typical laser welded joint of the present invention;

[0036] Figure 2 FIG. 1 is a schematic cross-sectional view of the steel plate parent material involved in the present invention;

[0037] Figure 3 Shown is a schematic diagram of the main steps of the laser welding joint manufacturing process involved in the present invention;

[0038] Figure 4 FIG2 is a schematic diagram of the steel plates involved in the present invention when they are butt-jointed;

[0039] Figure 5Shown is a schematic diagram of the laser welding process involved in the present invention;

[0040] Figure 6 FIG2 is a schematic top view of the laser welding process involved in the present invention;

[0041] Figure 7 Shown is a schematic cross-sectional view of the initial weld obtained in the present invention;

[0042] Figure 8 Another cross-sectional schematic diagram of the initial weld obtained in the present invention is shown;

[0043] Figure 9 FIG. 1 is another schematic cross-sectional view of the initial weld obtained in the present invention;

[0044] Figure 10 FIG. 1 is another schematic cross-sectional view of the initial weld obtained in the present invention;

[0045] Figure 11 The figure shows the metallographic cross section of the final weld obtained in a specific embodiment of the present invention;

[0046] Figure 12 Shown is the invention involved in Figure 11 The state of the welded joint obtained in the embodiment after tensile failure;

[0047] Figure 13 Shown is a metallographic cross section of a final weld obtained in another specific embodiment of the present invention;

[0048] Figure 14 Shown is the invention involved in Figure 13 The state of the welded joint obtained in Example after tensile failure. DETAILED DESCRIPTION

[0049] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the present invention is further described below with reference to specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. Furthermore, the accompanying drawings are schematic diagrams, and thus the devices and apparatuses of the present invention are not limited by the dimensions or proportions of the schematic diagrams.

[0050] It should be noted that in the claims and description of this patent, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprising a" does not exclude the presence of other identical elements in the process, method, article or device comprising the element. In the present invention, "5C+Mn" is 5 times the C content plus the sum of the Mn content.

[0051] The present invention provides a solder for laser welding steel plates with aluminum or aluminum alloy coatings. The solder composition, by weight percentage, satisfies the following requirements: C ≥ 0.5%, trace alloying elements 0-0.36%, Mn ≤ 2% (preferably ≤ 1.5%), Si ≤ 2% (preferably ≤ 1.5%, more preferably ≤ 1.0%), 6% ≥ 5C + Mn ≥ 2.5%, with the remainder being Fe and other unavoidable elements. The trace alloying elements are at least one of Nb, V, and Ti, with the contents of each not exceeding 0.12%. The solder, other than Fe and C, is not required. Mn and Si are generally added to the solder during wire processing to suppress defects such as oxides and improve processability. Preferably, the Si content does not exceed 1.0%, and the Mn content does not exceed 1.5%. The solder can be in various forms, such as wire, powder, or sheet; for example, solid wire or flux-cored wire.

[0052] Now refer to Figure 1The figure shows a laser welded joint 2 according to the present invention. It is formed by butting two steel base materials (a first steel plate 11 and a second steel plate 12) and then laser welding them. At least one of the first and second steel plates 11, 12 has an aluminum coating on one surface. When viewed along a cross-section of the weld, the joint exhibits the following characteristics: The weld is composed of lath martensite 21, which accounts for no less than 90% by volume, and contains no more than 10% austenite 22. Preferably, the lath martensite content is no less than 92%. In a preferred embodiment, the martensite content in the weld exceeds 95%, and in an even more extreme case, it can be entirely lath martensite. Furthermore, the final weld may contain trace amounts of carbides in addition to lath martensite and austenite. The distribution and size of retained austenite within the weld can take various forms, and the presence of a trace amount of austenite in the weld ensures that the TRIP effect occurs during weld load-bearing, transforming austenite into martensite, providing the weld with additional plasticity and ensuring sufficient strength. The average mass fraction of carbon within the weld is no less than 0.28%, and the average mass fraction of carbon is no less than 120% of the carbon content of the steel plate base material, generally ranging from 120% to 400% of the base material, and preferably from 130% to 250%. The carbon is primarily present in the weld in the form of a solid solution. The average mass fraction of aluminum in the weld is 0.72% to 1.2%. The absolute difference between the average mass fraction of manganese in the weld and the base material manganese content does not exceed 1.5%, preferably no more than 1%. The weld may also contain at least one of Si, Cr, Mo, and Ni, derived from the steel plate base material, with the average mass fraction of Si being 0.2-1.0%. However, elements such as Cr and Mo are not essential, and their content is generally less than 1.0%, preferably less than 0.6%, and they are primarily derived from the base metal. Ni is also not essential in the weld, and its content does not exceed 1.0%, preferably not exceeding 0.8%. It is worth mentioning that the weld may also contain trace amounts of Nb, V, and Ti alloying elements to provide precipitation strengthening and grain refinement. The content of each element is generally less than 0.12%, and these elements can be derived from the steel base metal or the solder, further improving the tensile properties of the joint.

[0053] The steel plate base material mentioned above generally has a coating on at least one side, such as Figure 2The first steel plate 11 shown has a first surface coating 111 and a second surface coating 112. Generally, the coating is composed of aluminum and silicon, wherein the aluminum content is not less than 85%, and preferably the aluminum content exceeds 90%. The thickness of the coating on each side is generally 10-50 μm. The steel plate base material is generally composed of ferrite and pearlite, wherein the carbon content is not less than 0.15%, and has a boron content of about 0.002-0.006% to meet the hardenability of the subsequent quenching process. It can form a fully martensitic structure after quenching and has high strength. The tensile strength of typical boron steel is not less than 1000 MPa. A typical steel plate base material, designated 22MnB5, contains the following elements by weight: 0.15% ≤ C ≤ 0.45%; 0.5% ≤ Mn ≤ 2.5%; 0.08% ≤ Si ≤ 0.4%; Al ≤ 0.45%; 0.01% ≤ Cr ≤ 0.5%; Ti ≤ 0.1%; Nb ≤ 0.1%; V ≤ 0.1%; S ≤ 0.05%; P ≤ 0.05%; 0.002% ≤ B ≤ 0.006%; the remainder being Fe and unavoidable impurities. The steel plate base material referred to in the present invention is various steel grades known in the art as hot stamping steel, boron steel, martensitic steel, etc., with varying carbon content or alloying elements. However, this is the raw material before quenching (stamping), and its thickness is generally 1.0-3.0 mm. This is well known in the art and will not be further described here. In addition, the welded joint can be formed by laser welding a first steel plate 11 and a second steel plate 12 with different thicknesses or different coating states, and their strength levels can also be different, that is, a combination of different thicknesses or different strengths. For example, the tensile strength of the steel plate base material can exceed 2000Mpa after hot stamping.

[0054] The manufacturing method of the laser welded joint 2 mentioned above mainly includes three steps: steel plate butt joint, laser welding and quenching treatment, such as Figure 3 shown.

[0055] In step 1, a set of first steel plates 11 and second steel plates 12 with aluminum coating to be welded are first provided, and then the first steel plates 11 and the second steel plates 12 are butt-welded, and there may be a gap or no gap between the first steel plates 11 and the second steel plates 12. Figure 4 As shown, the assembly gap width B is generally between 0-0.5mm.

[0056] In step 2, laser welding is performed on the assembled steel plates, such as Figure 5As shown. A laser beam 3 and solder 4 are provided and transported to the butt joint position and travel along the welding path at a certain welding speed. The laser beam 3 melts the first steel plate 11, the second steel plate 12 and the solder 4 to form an initial weld 6 on the travel path. During the laser welding process, the melting volume of the two steel plates is V1, the volume of the solder in the molten pool is V2, V1 and V2 satisfy 0.03≤V2 / V1≤0.6, and the solder 4 is the laser welding solder of the present invention. The relative position between the solder 4 and the laser beam 3 can include various types, including coaxial transport or off-axis transport, which is well known in the art. During the laser welding process, the laser beam 3 is generally emitted by a laser, wherein the laser can include various types, such as solid-state laser beams or gas laser beams, specifically including fiber lasers, disk lasers, semiconductor diode lasers and Nd:YAG-type solid-state lasers, or CO2 gas lasers. Of course, other types can also be included, as long as they can generate a laser beam and form a keyhole and a molten weld pool. Figure 6 The figure shows a schematic top view of the welding process, wherein 5 is a molten weld pool formed by the first steel plate 11, the second steel plate 12 and the solder 4 under the action of the laser beam, and 6 is the initial weld formed after cooling and solidification. The laser beam during the welding process may also be composed of one or more light spots, and the beam energy distribution may be in various forms such as Gaussian distribution, average distribution or dot ring distribution. During the welding process, the laser beam may also be fixed or synchronously move at high speed in various forms such as swinging along the welding direction. At this time, the swing shape may include various shapes such as circle, broken line, figure 8, ∞, etc. The swing frequency is generally 50-500HZ, and the swing amplitude is between 0.2-1.5mm. During the welding process, a variety of single or mixed shielding gases may be added, such as Ar gas, He gas, etc., or the welding process may be carried out without shielding gas.

[0057] During the welding process, solder can be added in a variety of ways, including powder or wire delivery. When delivered via wire, this is laser wire welding, which is well known in the art. The wire feeder can be, for example, MAG (metal active gas), MIG (metal inert gas), or TIG (tungsten inert gas) as a feeder. The welding wire can be solid or flux-cored. Adding solder via flux-cored wire or powder makes it easier to control the composition ratio, which is also well known in the art. Solder addition can also be accomplished by combining two different devices, such as two feeder devices, each delivering a different solder: one delivering a solder containing a certain composition and the other delivering a solder with a different composition. The combination of the two solders ensures that the solder ultimately delivered to the molten pool has the desired composition ratio. Alternatively, solder 4 can be added through multiple steps or components. For example, solder 4 can be composed of three separate solder wires, and the average mass composition of the three solders can meet the requirements of the present invention. The three solders can be added simultaneously, one primarily composed of Fe, one primarily composed of C, and one primarily composed of Mn and / or Si. Furthermore, solder addition can be performed in multiple steps, such as in a sequential manner, to ensure that the final weld microstructure comprises more than 90% lath martensite. Using a variety of solder wire combinations will further facilitate welding wire manufacturing and reduce the difficulty of wire production.

[0058] In the present invention, the regulation of different melting amounts is achieved by matching the laser welding speed with the welding wire feeding speed and controlling the welding wire composition. In the present invention, the welding speed and the wire feeding speed are controlled so that the initial weld front side reinforcement h10 and the initial weld back side reinforcement h11 on both sides of the initial weld obtained by welding do not exceed 0.3mm, which can be estimated based on the wire diameter, welding speed and wire feeding speed. Generally, the welding speed S1 is not less than 2.5m / min, and the wire diameter is d, which is generally 0.6-1.6mm, more commonly 1.0-1.2mm, which is generally more than 2 times the assembly gap width B. In the present invention, assuming that the average width of the upper and lower surfaces of the weld formed is B1, the wire feeding speed of the welding wire is S0, and the average thickness of the two steel plates is t, it is necessary to satisfy 0.04≤ ≤0.3; generally S0 is 1.0-4.5m / min, and its ratio to the welding speed is generally 40%-150%; thus ensuring that the initial weld front height h10 and the initial weld back height h11 after welding do not exceed 0.3mm. Generally speaking, the heights on both sides of the initial weld section are of an overall dome-shaped morphology that is higher than the base surface of the steel plate. The volume of the melted solder during the entire process is V2, including the case with or without gaps; and the total volume melted by the steel plate base material is V1; it satisfies 0.03≤V2 / V1≤0.6, and more narrowly 0.04≤V2 / V1≤0.45, and the entire weld volume is composed of V1 and V2. The average width B1 of the upper and lower surfaces of the weld is generally between 0.5mm and 4.0mm, B10 is the width of the upper surface of the initial weld, and B11 is the width of the lower surface of the initial weld. Such as Figure 7 The figure shows a schematic cross-sectional view of the initial weld obtained after laser welding. The cross-sectional morphology of the initial weld formed can include various types; Figure 7 The overall shape is shown as X; it can also include a Y-shaped or U-shaped shape; Figure 8 、 9 The following are schematic diagrams of Y-shaped and U-shaped welds, and their specific shapes can be adjusted by matching the process parameters of the laser welding process. Figure 10 The figure shows a schematic diagram when the thickness of the first steel plate t1 and the thickness of the second steel plate t2 are different. Generally, the internal structure of the initial weld is mainly martensite and retained austenite, with the martensite content being higher. Since the addition of solder containing the element carbon to the weld will inevitably cause the complete austenitization temperature of the weld to differ from that of the base material, the weld austenitization temperature Ac31 must not deviate from the steel plate base material austenitization temperature Ac30 by more than 100°; and the weld martensite transformation start temperature Ms1 must not deviate from the steel plate base material martensite transformation start temperature Ms0 by more than 100°. This ensures that after hot stamping and quenching, the carbon content in the weld is no less than 120% of that in the base material, and the carbon content is no less than 0.28%. The volume fraction of retained austenite in the weld does not exceed 10%, and more narrowly, no more than 5%. The retention of some retained austenite can enhance joint performance by generating a TRIP effect during subsequent stress loading.

[0059] During the hot stamping (quenching) process, the initial weld is ensured to be fully austenitized at the heating and holding temperatures. Typically, the temperature is 880-980°C, and the holding time is 90-500 seconds. After the holding period, rapid cooling is performed. This process can be achieved using a rapid cooling die or a liquid medium, with a cooling rate generally not less than 25°C / s. When using a die for stamping and cooling, various formed parts, including flat plates and part-shaped parts, can be formed, using either a flat die or a forming die. When using a flat die for stamping and cooling, the initial weld reinforcement morphology flattens under the pressure. The resulting front and back reinforcements h1 and h2 are reduced compared to the initial front and back reinforcements h10 and h11, respectively. When the surface reinforcements are approximated as a rectangular cross-section, the following mathematical formula is satisfied: 0.02 ≤ (h1 + h2) / (t1 + t2) ≤ 0.15. The inventive method, solder and weld joint can be used to manufacture components including hot stamped steel applications, such as various vehicles.

[0060] The technical solution of the present invention will be described in detail and completely through specific implementation methods below.

[0061] Example 1

[0062] like Figure 11 Shown is a cross-sectional view of the final weld obtained using the method of the present invention after laser welding and quenching. The starting material used for the weld is 22MnB5 hot-formed steel with an aluminum-silicon coating approximately 30μm thick on both the upper and lower surfaces, exhibiting a strength exceeding 1500 MPa after quenching. The base material has a carbon content of approximately 0.23%, a manganese content of approximately 1.05%, and a thickness of 1.5mm. The final weld is generally X-shaped, with a lath martensite content of approximately 96%, a carbon mass fraction of approximately 0.28%, an average aluminum mass fraction of approximately 0.72%, a manganese content of approximately 0.96%, and a silicon content of approximately 0.52%. The carbon content is higher than that of the starting material, approximately 122% of the base material. The final double-sided widths of the weld are approximately 2.80mm and 2.26mm, respectively, which are obtained by stamping with a flat die during quenching. The final front and back excess heights of the weld are approximately 0.10mm and 0.14mm, respectively. In the welding wire added during the welding process, C accounts for 0.62% of the welding wire mass fraction, Mn accounts for approximately 0.48% of the welding wire mass fraction, and Si accounts for 0.2% of the welding wire mass fraction. Except for iron, the rest are inevitable P and S elements, and their contents are all less than 0.015%. The diameter of the welding wire used is 1.0mm, and the laser filling welding method is used to manufacture the welded plate. The assembly gap width B is 0mm, the welding speed S1 is 3.0m / min, the wire feeding speed S0 is 2.4m / min, and the average melting volume V1 of the two steel plates per minute is approximately 11400mm.3 The average volume V2 of solder in the molten pool melted per minute is estimated to be about 1885mm according to the wire feeding speed. 3 , V2 / V1 ≈ 0.165, satisfying 0.03 ≤ V2 / V1 ≤ 0.6. After welding, the initial weld was placed in a heating furnace at 930°C for approximately 300 seconds. It was then hot stamped under a flat die at a cooling rate of approximately 40°C / s and cooled to form a laser welded joint. Figure 12 The following table shows the mechanical properties of the laser welded joints after standard tensile testing. The results show that all specimens failed in the base metal region, with an average fracture strength of approximately 1444 MPa and an elongation at break of 9.31%.

[0063] Example 2

[0064] like Figure 13 Shown is a cross-sectional view of the final weld obtained using the method of the present invention after laser welding and quenching. The starting material used for the weld is 22MnB5 hot-formed steel, with aluminum-silicon coatings approximately 30μm thick on both the upper and lower surfaces. The steel has a strength exceeding 1500 MPa after quenching. The base metal has a carbon content of approximately 0.23%, a manganese content of approximately 1.05%, and a thickness of 1.5mm. The final weld is an overall X-shaped weld. The lath martensite content within the weld is approximately 95%, and the mass fraction of carbon in the weld is approximately 0.29%, approximately 126% of that in the base metal. The average mass fraction of aluminum is approximately 1.2%, the manganese content is approximately 1.0%, and the silicon content is approximately 0.55%. The final double-sided widths of the weld are approximately 2.78mm and 2.08mm, respectively, which are obtained by stamping with a flat die during quenching; the final front and back excess heights of the weld are approximately 0.11mm and 0.15mm, respectively; in the welding wire added during the welding process, C accounts for approximately 0.65% of the welding wire mass fraction, Mn accounts for 1.0% of the welding wire mass fraction, and Si accounts for 0.25% of the welding wire mass fraction. Except for iron, the rest are inevitable P and S elements, and their contents are all less than 0.02%. The diameter of the welding wire used is 1.0mm, and the laser filling welding method is used to manufacture the welded plate; the assembly gap width B is 0.1mm, the welding speed S1 is 3.0m / min, the wire feeding speed S0 is 2.4m / min, and the average melting volume V1 of the two steel plates per minute is approximately 10950mm 3 The average volume V2 of solder in the molten pool melted per minute is estimated to be about 1885mm according to the wire feeding speed. 3, V2 / V1 ≈ 0.172, satisfying 0.03 ≤ V2 / V1 ≤ 0.6. After welding, the initial weld was placed in a heating furnace at 930°C for approximately 300 seconds. It was then hot stamped under a flat die at a cooling rate of approximately 40°C / s and cooled to form a laser welded joint. Figure 14 The following table shows the mechanical properties of the laser welded joints after standard tensile testing. The results show that all specimens failed in the base metal region, with an average fracture strength of approximately 1458 MPa and an elongation at break of 7.37%.

[0065] Example 3

[0066] A final weld seam obtained using the method of the present invention after laser welding and quenching. The base material used for the weld is 22MnB5 hot-formed steel, with aluminum-silicon coatings approximately 30 μm thick on both the upper and lower surfaces and a strength exceeding 1500 MPa after quenching. The base material has a carbon content of approximately 0.23% and a manganese content of approximately 1.05%, and is 1.5 mm thick. The final weld is X-shaped as a whole, with the lath martensite content in the weld being about 95%, the mass fraction of the C element in the weld being about 0.3%, which is about 130% of the base material, the average mass fraction of the aluminum element being about 1.2%, the Mn element content being about 1.0%, and the Si element content being about 0.95%; the widths of the final weld on both sides are approximately 2.82 mm and 2.32 mm, respectively, which are obtained by stamping with a flat die during quenching; the final weld front and back reinforcements are approximately 0.12 mm and 0.16 mm, respectively; among the welding wires added during the welding process, C accounts for about 0.5% of the welding wire mass fraction, Mn accounts for 1.0% of the welding wire mass fraction, and Si accounts for 2% of the welding wire mass fraction. Except for iron, the rest are unavoidable P and S elements, and their contents are all less than 0.02%. The diameter of the welding wire used is 1.0 mm, and the laser wire-filling welding method is used to manufacture the tailor-welded blanks. The assembly gap width B is 0.1 mm, the welding speed S1 is 3.0 m / min, the wire feeding speed S0 is 2.4 m / min, and the average melting volume V1 of the two steel plates per minute is about 10950 mm. 3 The average volume V2 of solder in the molten pool melted per minute is estimated to be about 1885mm according to the wire feeding speed. 3 , V2 / V1 ≈0.172, satisfying 0.03≤V2 / V1 ≤0.6. After welding, the initial weld is placed in a heating furnace, heated to 930°C, and kept warm for about 300s. Subsequently, the laser welded joint is obtained by hot stamping and cooling under a flat mold at a cooling rate of about 40°C / s. The obtained laser welded joint is prepared through standard tensile test specimens and then subjected to mechanical property testing. The results show that all the specimens broke and failed in the base material area, with an average fracture strength of about 1425Mpa and an elongation at fracture of 7.28%.

[0067] Example 4

[0068] A final weld seam obtained using the method of the present invention after laser welding and quenching. The base material used for the weld is 22MnB5 hot-formed steel, with aluminum-silicon coatings approximately 30 μm thick on both the upper and lower surfaces and a strength exceeding 1500 MPa after quenching. The base material has a carbon content of approximately 0.23% and a manganese content of approximately 1.05%, and is 1.5 mm thick. The final weld is X-shaped as a whole, with the lath martensite content in the weld being about 95%, the mass fraction of the C element in the weld being about 0.3%, which is about 130% of the base material, the average mass fraction of the aluminum element being about 1.1%, the Mn element content being about 1.0%, and the Si content being about 0.57%; the widths of the final weld on both sides are approximately 2.73 mm and 2.01 mm, respectively, which are obtained by stamping with a flat die during quenching; the final weld front and back reinforcements are approximately 0.12 mm and 0.15 mm, respectively; among the welding wires added during the welding process, C accounts for about 0.8% of the welding wire mass fraction, Mn accounts for 2% of the welding wire mass fraction, and Si accounts for 0.25% of the welding wire mass fraction. Except for iron, the rest are unavoidable P and S elements, and their contents are all less than 0.02%. The diameter of the welding wire used is 1.0 mm, and the laser wire-filling welding method is used to manufacture the tailor-welded blanks. The assembly gap width B is 0.1 mm, the welding speed S1 is 3.0 m / min, the wire feeding speed S0 is 1.8 m / min, and the average melting volume V1 of the two steel plates per minute is about 10665 mm. 3 The average volume V2 of solder in the molten pool melted per minute is estimated to be about 1414 mm according to the wire feeding speed. 3 , V2 / V1 ≈0.133, satisfying 0.03≤V2 / V1 ≤0.6. After welding, the initial weld is placed in a heating furnace, heated to 930°C, and kept warm for about 300s. Subsequently, the laser welded joint is obtained by hot stamping and cooling under a flat mold at a cooling rate of about 40°C / s. The obtained laser welded joint is prepared by standard tensile test specimens and then subjected to mechanical property testing. The results show that all the specimens broke and failed in the base material area, with an average fracture strength of about 1503Mpa and an elongation at fracture of 7.56%.

[0069] All samples of laser welded joints in all embodiments fractured and failed in the base material area, with a fracture strength greater than 1400 MPa and an elongation greater than 7%. They have very high mechanical properties and can meet the production and manufacturing of related parts.

[0070] Comparative Example

[0071] When the same welding raw materials as in Example 1 were used, welding was performed without filler wire, and different surface treatments were performed, all the welded joints in the comparative example broke and failed at the weld position, failing to meet the use requirements. The relevant mechanical properties are as follows:

[0072] Table 1

[0073] Coating condition Breaking strength (Mpa) (GB / T 2651-2008) Elongation (%) (GB / T 2651-2008) Comparative Example 1 No coating removed on both sides 1372 1.83 Comparative Example 2 Upper surface removal 1387 2.06 Comparative Example 3 Lower surface removal 1405 2.52

[0074] All documents mentioned in this application are incorporated herein by reference, just as if each document were incorporated herein by reference individually. It should also be understood that after reading the above teachings of the present invention, those skilled in the art may make various changes or modifications to the present invention, and that such equivalents also fall within the scope of the claims appended hereto.

Claims

1. A laser welding solder for laser welding joints, characterized in that: The composition of the solder satisfies the following requirements by weight percentage: C ≥ 0.5%, trace alloying elements 0-0.36%, Mn and Si contents both ≤ 2%, 6% ≥ 5C + Mn ≥ 2.5%, and the remainder being Fe and other unavoidable elements; the trace alloying elements are at least one of Nb, V, and Ti, and the contents of Nb, V, and Ti do not exceed 0.12%.

2. A solder according to claim 1, characterized in that Si content ≤1%.

3. A solder according to claim 1, characterized in that 1%≤Mn content≤2%.

4. A laser welded joint, wherein when two steel plates are butt-jointed and laser welded, the laser welding filler metal according to any one of claims 1 to 3 is added to the molten pool to form an initial weld, and the initial weld is quenched to form the laser welded joint, wherein at least one of the steel plates is a steel plate with an aluminum coating or an aluminum alloy coating, and wherein: The final weld of the laser welded joint meets the following conditions: the volume fraction of the internal lath martensite is not less than 90%, the average mass fraction of the solid solution strengthening element C is not less than 0.28%, the average mass fraction of the Al element is 0.72%~1.2%, and the average mass fraction of the C element is not less than 120% of the C content of the steel plate base material.

5. The laser welded joint according to claim 4, wherein: The average mass fraction of the C element of the final weld is 120% to 400% of the C content of the steel plate base material, and the absolute value of the difference between the average mass fraction of the Mn element and the Mn element content of the steel plate base material does not exceed 1.5%.

6. The laser welded joint according to claim 4, wherein: The volume fraction of the lath martensite is not less than 92%.

7. The laser welded joint according to claim 4, wherein: The final weld front side reinforcement h1 and the final weld back side reinforcement h2 formed by the laser welding joint do not exceed 0.3 mm, and the quenching method is die stamping cooling.

8. A method for manufacturing a laser welded joint, characterized in that: The method comprises the following steps: Step 1: Provide two steel plate base materials, at least one of which is a steel plate with aluminum coating or aluminum alloy coating, and butt the two steel plates together; Step 2: performing laser welding on the butt-jointed steel plates, wherein during the welding process, the solder according to claim 1 is added to the molten pool to form an initial weld; Step 3: quenching and cooling the initial weld to obtain the laser welded joint according to any one of claims 4 to 7; During the laser welding process in step 2, the melting volume of the two steel plates is V1, the volume of the solder in the molten pool is V2, and V1 and V2 satisfy 0.03≤V2 / V1≤0.

6.

9. The method according to claim 8, wherein: In step 2, the solder is a welding wire, and the welding speed S1 and the wire feeding speed S0 during the welding process satisfy the following relationship: 0.04≤ ≤0.3, where d is the wire diameter, d ranges from 0.6-1.6mm and exceeds twice the assembly gap width B, B ranges from 0-0.5mm, S1 is not less than 2.5m / min, B1 is the average width of the upper and lower surfaces of the weld formed, S0 ranges from 1.0-4.5m / min, and t is the average thickness of the two steel plates.

10. A high-strength steel workpiece, characterized in that The high-strength steel workpiece is composed of two steel plate base materials and a laser welding joint as described in any one of claims 4 to 7 for connecting the base materials; when the high-strength steel workpiece is subjected to a tensile test, it breaks and fails in the base material area, and the elongation at break is not less than 5%.

Citation Information

Patent Citations

  • Method of producing a welded part having very high mechanical properties from a rolled and coated sheet

    CN101426612B

  • Coated steel strips, methods of making the same, methods of using the same, stamping blanks prepared from the same, stamped products prepared from the same, and articles of manufacture which contains

    CN101583486B

  • Welded plates and their manufacturing methods, and hot-stamped parts using welded plates

    CN104023899B

  • Method for laser welding one or more workpieces of hardenable steel with a butt joint using a filler wire

    CN104994989A

  • Steel welding component with aluminum or aluminum alloy coating and manufacturing method thereof

    CN106334875A

Cited By

  • A laser welding method for a high-strength steel workpiece with a plated layer, a laser welding joint and application thereof

    CN122606155A